Radiographic Comparison of the Mechanical Axis Including Calcaneus to the Conventional Mechanical Axis in Medial Unicompartmental Knee Arthroplasty - Kuroda, Yuichi; Takayama, Koji; Ishida, Kazunari; Hayashi, Shinya; Hashimoto, Shingo; Tsubosaka, Masanori; Kamenaga, Tomoyuki; Matsushita, Takehiko; Niikura, Takahiro; Kuroda, Ryosuke; Matsumoto, Tomoyuki (The Journal of Knee Surgery, 2019)
Since a hindfoot alignment is not included in the conventional mechanical axis (hip–ankle [HA] line), a mechanical axis including the calcaneus (hip–calcaneus [HC] line) has recently attracted attention as an alternative weight-bearing line. However, there are few reports on unicompartmental knee arthroplasty (UKA) regarding the HC line. Therefore, this study aimed to compare postoperative alignments after UKA between the HA line and the HC line. Postoperatively, HC radiographs were taken in 88 consecutive patients who underwent medial UKA. The hip–knee–ankle (HKA) and hip–knee–calcaneus (HKC) angles were compared in the same patient. Regarding tibial inclination, the conventional tibial component–ankle (TCA) angle was compared with reference to the HC line (tibial component–calcaneus [TCC] angle). The mean postoperative HKA and HKC angles were 2.8 ± 2.7 and 2.0 ± 2.5 degree, respectively. The mean postoperative TCA and TCC angles were 87.7 ± 2.1 and 88.5 ± 2.1 degree, respectively. There were significant differences between the two groups in both lower limb alignment and tibial component angle. The present study indicated that the HKC and the TCC angles significantly decreased the varus alignment by approximately 1 degree compared with the HKA and TCA angles. Neutral in the HA line corresponds to valgus in reference to the HC line, which may result in overcorrection. Surgeons should consider evaluating the HC line in place of the HA line, which may affect preoperative planning and postoperative outcome during UKA. This is a Level II, diagnostic study.
Keywords: unicompartmental knee arthroplasty; hip–knee–calcaneus angle; mechanical axis; hindfoot alignment